Tax Planning And Tax Aggressiveness Before And After The Implementation Of Psak 73 (Study On Service Companies In The Retail Trade And Financing Subsectors For The 2017-2022 Period) - Ramadhina Aila Putri; Sudrajat Sudrajat (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research will provide knowledge regarding tax planning and tax aggressiveness before and after the implementation of PSAK 73. The population used in this research is service sector companies with retail trade & financing company subsectors that have gone public information and are listed on the Stock Exchange. Indonesian Securities (BEI). This research uses data analysis methods including descriptive statistical analysis, normality testing, and hypothesis testing. This test was tested using the Microsoft Excel application and the Statistical Package for the Social Sciences (SPSS) software version 27. The results of the research show that Tax Planning has improved: Implementation of PSAK 73 has had a significant impact on tax planning behavior in retail trade and financing services companies and The research results also show that there is a significant difference in the level of tax aggressiveness before and after the implementation of PSAK 73.